Вплив параметрів сітки скінчених елементів при моделюванні процесу вирубування деталей в середовищі DEFORM 3D - Бень, І. В.; Орлюк, М. В. (НТУ "ХПІ", 2015)
В роботі досліджується вплив параметрів моделювання процесу вирубування (пробивання) в програмному середовищі DEFORM 3D на достовірність результатів, для оцінки результатів використані експериментальні та теоретичні данні. Для порівняння обрано найбільш важливі параметри процесу завдяки яким можна провести аналіз. Відзначається значний вплив параметрів сітки скінчених елементів на результати моделювання, так для отримання достовірних результатів сітка має складатись із рівновісних елементів, ущільнених в осередку деформації.

The theoretical research of the influence of parameters modeling the process of cutting (punching) in DEFORM 3D software environment on the reliability of the results is described in the article. For an estimation of the results experimental and theoretical data is used. In order to make a comparison the most important parameters of the process, which can enable carrying out an analysis, were chosen. A significant effect of the parameters of finite elements mesh on the simulation results is mentioned. In that way, to obtain reliable results, the mesh should consist of equiaxed elements which are compacted in the deformation zone.
The influence of parameters of finite element mesh in the simulation of the blanking (punching) process of details in DEFORM 3D software
Keywords: вирубка; комп'ютерне моделювання; критерій руйнування; деформація; компоненти напружень; перестроювання сітки; сколююча тріщина; cutting; computer simulation; finite elements mesh; criterion of destruction; deformation; stress components; meshing; shear bursting